The impact of the introduction of selective screening in the UK on the epidemiology, presentation, and treatment outcomes of developmental dysplasia of the hip - Arwel T. Poacher; Isaac Hathaway; Daniel L. Crook; Joseph L. J. Froud; Lily Scourfield; Catherine James; Matthew Horner; Eleanor C. Carpenter (Bone & Joint Open, 2023)
Aims: Developmental dysplasia of the hip (DDH) can be managed effectively with non-surgical interventions when diagnosed early. However, the likelihood of surgical intervention increases with a late presentation. Therefore, an effective screening programme is essential to prevent late diagnosis and reduce surgical morbidity in the population. Methods: We conducted a systematic review and meta-analysis of the epidemiological literature from the last 25 years in the UK. Articles were selected from databases searches using MEDLINE, EMBASE, OVID, and Cochrane; 13 papers met the inclusion criteria. Results: The incidence of DDH within the UK over the last 25 years is 7.3/1,000 live births with females making up 86% of the DDH population (odds ratio 6.14 (95% confidence interval 3.3 to 11.5); p < 0.001). The incidence of DDH significantly increased following the change in the Newborn and Infant Physical Examination (NIPE) guidance from 6.5/1,000 to 9.4/1,000 live births (p < 0.001). The rate of late presentation also increased following the changes to the NIPE guidance, rising from 0.7/1,000 to 1.2/1,000 live births (p < 0.001). However, despite this increase in late-presenting cases, there was no change in the rates of surgical intervention (0.8/1,000 live births; p = 0.940). Conclusion: The literature demonstrates that the implementation of a selective screening programme increased the incidence of DDH diagnosis in the UK while subsequently increasing the rates of late presentation and failing in its goal of reducing the rates of surgical intervention for DDH. Cite this article: Bone Jt Open 2023;4(8):635–642.